Wastewater Reuse for Irrigation: Evaluation of Salinisation Risk - Marinova, Svetla; Kathijotes, Nicholas (My University, 2003)
Under the drought conditions occurring around the Mediterranean region, the use of treated effluents resulting from treatment of domestic effluents may be an important resource. Using however non-conventional quality water presents a number of ecological and health risks and poses problems connected with soil and ground water contamination. This paper concentrates in evaluating the possible salinisation risks encountered on the soil profile as a result of using the above effluent and suggests possible corrective management techniques.
Keywords: Treated sewage; Wastewater; Salinity; Salinisation; Salinity